EFEKTIVITAS PELATIHAN DALAM UPAYA MENINGKATKAN KUALITAS PELAYANAN BUTLER DI THE SEMAYA BALI - I Made Sucipta Adnyana, SE.MM (Jurnal Ilmiah Hospitality Management, 2014)
The training is aimed to know the effectiveness of a butler in order to increase service to guest. This research using technical or descriptive qualitative data explained which has been collected logically and accompanied by arguments to be a conclusion. Intrumen used in collecting data of a questionnaire that is to put the question to writing systematically the butler and analysis by the use of the scale based on an assessment likert scale. Overall ability of a butler included in the category of good enough. And training programs already run includes in good category. But there ' s some things to be stepped up, adding that the training the material to fit the needs of a butler.